Comparative transcriptomic profiling reveals differentially expressed genes and important related metabolic pathways in shoots and roots of a Saudi wheat cultivar (Najran) under salinity stress - Alyahya, Norah; Taybi, Tahar (Frontiers in Plant Science, 2023)
High salinity of soil is a threatening constraint for agricultural output worldwide. The adverse effects of salt stress on plants can be revealed in different manners, from phenotypic to genetic changes. A comparative RNA-Sequencing analysis was done in roots and shoots of bread wheat, Najran cultivar between plants grown under unstressed control condition (0 mM NaCl) and salt treatment (200 mM NaCl). More than 135 million and 137 million pair-end reads were obtained from root and shoot samples, respectively. Of which, the mapped reads to Triticum aestivum genome IWGSC_V51 (accessed Nov. 2021) ranged from 83.9% to 85% in the roots and 71.6% to 79% in the shoots. Interestingly, a comparison of transcriptomic profiling identified that total number of significantly differentially expressed genes (DEGs) in the roots was much higher than that found in the shoots under NaCl treatment, 5829 genes were differentially expressed in the roots whereas 3495 genes in the shoots. The salt-induced change in the transcriptome was confirmed by RT-qPCR using a set of randomly selected genes. KEGG enrichment analysis classified all DEGs in both roots and shoots into 25 enriched KEGG pathways from three main KEGG classes: metabolism, organismal systems and genetic information processing. According to that, the most significantly regulated pathways in the root and shoot tissues were glutathione metabolism and biosynthesis of secondary metabolites such as phenylpropanoids and galactose metabolism suggesting that these pathways might participate in wheat salt tolerance. The findings highlight the importance of the control of oxidative stress via Glutathione and phenylpropanoids and the regulation of galactose metabolism in the roots and shoots for salttolerance in wheat. They open promising prospects for engineering salt-tolerance in this important crop via targeted improvement of the regulation of key genes in the production of these compounds.This is a provisional file, not the final typeset article production, is currently challenged by salinity stress that causes up to 40% yield loss, seriously compromising global food security (Singh, et al., 2020).